THE EFFECT OF STORYTELLING TOWARDS STUDENTS' SPEAKING SKILL AT X GRADE STUDENTS OF MA NURUL HARAMAIN BOARDING SCHOOL - Yunita Hidayati (Journal of Languages and Language Teaching, 2019)
This study was aimed to investigate whether or not the use of storytelling has positive effect towards the students' speaking skills at the tenth-grade students of MA Nurul Haramain. The form of this research was pre-experimental study with comparing the scores in pre-test and post-test. The population of this research is the tenth-grade students of MA Nurul Haramain Narmada, with the sample is class X B that consists of 21 students. The research findings show that the mean score of the pre-test is 59.05 and the mean score of post-test is 78.48. It shows that storytelling has a significant impact towards the students' speaking skill. The result of sig. 2-tailed (0.00) is lower than sig. level (0.05), also the result of the t-test is higher than t-table, the value is 4.1 >1.6 it means that the alternative hypothesis (Ha) is accepted. It can be concluded that there is a highly significant effect of storytelling technique towards students' speaking skill on the tenth-grade students of MA Nurul Haramain.